Distribution of stream macroalgae in three tropical drainage basins of southeastern Brazil - Branco, LHZ; Junior, O. N. (E Schweizerbart'sche Verlags, 1998)
Three drainage basins belonging to different drainage systems, but in close proximity, were evaluated to compare the distribution of macroalgal communities in the northwest region of São Paulo State, southeastern Brazil. Monthly samplings were carried out from September 1992 through September 1993 in three sites along the main river of each basin. 10 m length cross segments were evaluated for species per cent cover and richness, on both the population and community levels. Selected stream variables were measured: specific conductance, temperature, turbidity, mean cross-sectional area of the reach, current velocity, pH, and oxygen saturation (%). Principal Coordinate Analysis (PCO), chi-square good-of-fitness, and Pearson Product-Moment correlation coefficient were applied to evaluate the distribution of the macroalgal species. The survey resulted in 36 taxa of macroalgae, of which Cyanophyta was the dominant group (17 taxa or 41.7% of the total), followed by Chlorophyta (15 taxa or 41.7%), Rhodophyta (3 taxa or 8.3%) and Chrysophyta (1 taxon or 2.8%). Stigeoclonium helveticum, 'Chantransia' stage of Batrachospermum spp., and B. delicatulum were the most widespread and frequent macroalgae throughout the basins. The analyses showed that conductance and current velocity were the factors most closely related to the distribution of the macroalgal species. Positive correlation between richness and percent cover was determined, which reinforces the patchiness of stream macroalgal distribution.